2014
DOI: 10.1172/jci71359
|View full text |Cite
|
Sign up to set email alerts
|

Central memory CD8+ T lymphocytes mediate lung allograft acceptance

Abstract: Memory T lymphocytes are commonly viewed as a major barrier for long-term survival of organ allografts and are thought to accelerate rejection responses due to their rapid infiltration into allografts, low threshold for activation, and ability to produce inflammatory mediators. Because memory T cells are usually associated with rejection, preclinical protocols have been developed to target this population in transplant recipients. Here, using a murine model, we found that costimulatory blockade-mediated lung a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 100 publications
8
115
0
Order By: Relevance
“…In addition, we observed that CD45RC high T cells were positive for CD45RA and CD4RB and negative for CD45RO, suggesting that targeting the CD45RC isoform would more specifically eliminate naive and TEMRA cells but would spare memory T cells and thus preserve memory immunity. In recent years, it has been shown that CD8 + and CD4 + Tregs can be or emerge from memory cells, challenging the dogma of memory cells being uniformly detrimental to graft survival and tolerance induction (50)(51)(52)(53)(54). Indeed, targeting CD45RC not only induced active Treg-mediated donor alloantigen-specific tolerance (i.e., no signs of chronic allograft rejection, inhibition of anti-donor humoral responses), but also preserved immunity toward new exogenous antigens and memory responses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed that CD45RC high T cells were positive for CD45RA and CD4RB and negative for CD45RO, suggesting that targeting the CD45RC isoform would more specifically eliminate naive and TEMRA cells but would spare memory T cells and thus preserve memory immunity. In recent years, it has been shown that CD8 + and CD4 + Tregs can be or emerge from memory cells, challenging the dogma of memory cells being uniformly detrimental to graft survival and tolerance induction (50)(51)(52)(53)(54). Indeed, targeting CD45RC not only induced active Treg-mediated donor alloantigen-specific tolerance (i.e., no signs of chronic allograft rejection, inhibition of anti-donor humoral responses), but also preserved immunity toward new exogenous antigens and memory responses.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, eosinophils can undergo either Th1-or Th2-induced polarization based on environmental cytokine milieu (22). While we and others have previously noted that IFN-γ and TNF-α, Th1-related cytokines, induce iNOS in several experimental models (11,23,24), very limited data exist on iNOS induction in eosinophils (25). In fact, some have suggested that Th2-polarizing cytokines, such as IL-4, may induce iNOS in this cell population (26).…”
Section: Cd11bmentioning
confidence: 95%
“…For example, while the local production of NO correlates with rejection of kidney (9) and heart allografts (10), recent work from our laboratories has demonstrated that NO plays a critical role in amelioration of lung allograft pathology (11). Specifically, the expression of recipient-derived type II NOS, or inducible NOS (iNOS), is a critical factor for CSB-mediated lung allograft acceptance (11). Myeloid cells have the capacity to express iNOS and were thus suspected as contributing to iNOS-mediated lung allograft acceptance (12).…”
Section: Introductionmentioning
confidence: 99%
“…For example, fluorodeoxyglucose PET (FDG-PET) can be used to monitor acute lung allograft rejection owing to a high rate of metabolism of graft-infiltrating T cells (65). Thus, the orthotopic mouse lung transplant model is an effective experimental platform to study mechanisms that contribute to AR, test noninvasive diagnostic modalities as well as to study immune tolerance (66), and evaluate strategies to prevent or treat this complication. AMR.…”
Section: Armentioning
confidence: 99%